The multilevel impacts of proximate crime generators and attractors on individual-level perceptions of crime risk - Houser, Kimberly (Crime & delinquency, 2019)
Fear of crime has been associated with mental illness, poor physical health, reduced social cohesion and informal social control. Prior studies examining variance in levels of fear have been explained at both the individual and neighborhood levels. Although there is a growing body of research examining the association between specific land uses and perceptions of risk, these studies have generally measured land uses individually rather than in a grouped theoretical context or in terms of homogeneous categories; the latter are hampered by inadequate theoretical application and a failure to recognize differences in the effects of land uses that share common characteristics. Using hierarchical linear modeling, the current study examined whether the proximity and volume of theoretically driven criminogenic land uses influence perceptions of crime risk.